Complication and Management of Cataract Surgery, a Retrospective Analysis - Zanaj, Violeta; Bani, Blerina (South Eastern European Journal of Public Health, 2024)
Cataract surgery is one of the most common ophthalmological procedures, essential for restoring vision in patients with cataracts. Despite its routine nature, factors such as demographic characteristics, comorbidities, and postoperative outcomes significantly. This study evaluates the treatment of cataracts through surgery and its postoperative progress, focusing on demographic factors, clinical presentation, diagnostic methods, and the prevalence of complications and pain following surgery. A retrospective cohort study was conducted using data from 89 patients who underwent cataract surgery at a private hospital in Tirana between December 2020 and August 2021. Data on demographic characteristics, associated comorbidities, diagnostic methods, duration of postoperative stays, complications, and pain levels were collected and analyzed. The majority of patients were male (62.92%), and the most affected age group was 66–71 years (30.34%). Comorbidities were present in 23.6% of patients, with diabetes mellitus (42.86%) and arterial hypertension (28.57%) being the most common. The diagnosis was confirmed in all cases via slit-lamp biomicroscopic with mydriasis. A postoperative hospital stay of one day was observed in 91.01% of patients, with complications occurring in only 3.37% of cases. Postoperative pain was predominantly mild, reported by 87.64% of patients. Cataract surgery is a highly effective and safe procedure, with minimal complications and a short recovery period. The findings underscore the importance of early detection, effective management of comorbidities, and standard diagnostic protocols to optimize patient outcomes in Albania.